Campus Readiness for Supporting International Student Success - Choudaha, Rahul (Journal of International Students, 2016)
American higher education is among the most preferred destinations for many globally mobile students. According to OECD (2016), the United States is the leading destination attracting 26% of all the globally mobile students followed by the United Kingdom (15%), France (11%), Germany (10%), and Australia (8%); yet the share of international students in the total enrollment at the tertiary level in the U.S. is only 4 %. One of the primary reasons for the attractiveness of American institutions is the perception of quality education among prospective students and its implications for a better career and life success. The terror attacks of September 11, 2001 resulted in a temporary decline in international student enrollment, which continued until 2005/06. Since then American higher education has shown resilience and the enrollment of international students has been growing at a healthy pace.